2003
DOI: 10.1074/jbc.m206568200
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Characterization and Crystal Structure of a Thermostable Cytochrome P450 from Thermus thermophilus

Abstract: The second structure of a thermophile cytochrome P450, CYP175A1 from the thermophilic bacterium Thermus thermophilus HB27, has been solved to 1.8-Å resolution. The overall P450 structure remains conserved despite the low sequence identity between the various P450s. The CYP175A1 structure lacks the large aromatic network found in the only other thermostable P450, CYP119, thought to contribute to thermal stability. The primary difference between CYP175A1 and its mesophile counterparts is the investment of charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 44 publications
2
83
0
Order By: Relevance
“…However, it is unrelated to the plant enzyme [70]. A P450 β-ring hydroxylase gene was also found in the carotenoid-containing thermophilic bacterium, Thermus thermophilus and the crystal structure has been solved [71]. The location of this single P450 gene on the thermophile's megaplasmid suggests that the gene may have been acquired through horizontal transfer and perhaps conferred some advantage to heat stress.…”
Section: What Is the Structural Basis For Enzyme Specificity?mentioning
confidence: 87%
“…However, it is unrelated to the plant enzyme [70]. A P450 β-ring hydroxylase gene was also found in the carotenoid-containing thermophilic bacterium, Thermus thermophilus and the crystal structure has been solved [71]. The location of this single P450 gene on the thermophile's megaplasmid suggests that the gene may have been acquired through horizontal transfer and perhaps conferred some advantage to heat stress.…”
Section: What Is the Structural Basis For Enzyme Specificity?mentioning
confidence: 87%
“…For example, mutagenesis studies and crystal structures showed that two aromatic clusters are important for the thermal stability of the thermophilic P450 119 from Sulfolobus solfataricus (Nishida and Ortiz de Montellano, 2005). However, the crystal structure of P450 175A1 shows that aromatic clusters are not present in this thermophilic P450, suggesting that its thermal stability is achieved through other mechanisms (Yano et al, 2003). Relatively little is known about the structural determinants of mammalian P450 stability.…”
Section: Discussionmentioning
confidence: 99%
“…The structures of P450s were determined by X-ray crystallography at high resolution (Poulos et al 1986;Hasemann et al 1994;Nakahara et al 1994;Cupp-Vickery and Poulos 1995;Li and Poulos 1997;Park et al 2000;Williams et al 2000a;Podust et al 2001;Podust et al 2003;Yano et al 2003). The structure of all enzymes resolved so far is very similar despite the low amino-acid sequence identity of < 20 % (Graham and Peterson 1999).…”
Section: P450 Monooxygenases: Whole Cell Oxidationsmentioning
confidence: 99%
“…All microbial P450 monooxygenases that are expressed in E. coli keep their activity during production and isolation. They yield 30-50 mg of active protein per liter in standard batch processes (Oster et al 1991;Bell et al 2001;Yano et al 2003). In some cases, the expression depends on the addition of the heme precursor aminolevulinic acid ).…”
Section: Production and Purificationmentioning
confidence: 99%